Policy of excises harmonization in the EU and EEU - A. V. Tikhonova (Russian Journal of Economics and Law, 2019)
Objective: to develop recommendations for improving the EAEU policy in the field of excise duties harmonization based on comparative characteristics of the types of harmonization policies applied in the EU and the EAEU.Methods: general methods of cognition (deduction and induction, analysis and synthesis, description and generalization) and specific scientific methods of cognition (comparison method, tabular and graphical method of data representation) were used. Results: the actively developing processes of globalization, international integration and digitalization cause the need to update and adapt national tax systems. At the same time, the global practice and theory of taxation demonstrate the absence of a unified approach to the harmonization of taxation, especially with regard to indirect taxation. In order to assess the mechanisms of tax harmonization, specific features of the policy of harmonization of excise taxes applied in the EU and the EAEU are considered, which, in particular, include the issues of harmonization of objects of taxation (excisable goods), tax base, tax rates and the mechanism of tax procedures. The effects and risks of the non-restrictive policy of the European Union and the restrictive excise policy of the EAEU are analyzed. The assessment of the actual results of harmonization in the integration associations under consideration allowed determining the priority areas of harmonization in the Eurasian space by using mixed-type policies.Scientific novelty: it consists in the development of theoretical and methodological foundations for the formation of a coherent excise policy within the Eurasian Economic Union, based on the advantages and disadvantages of two types of harmonization policies (restrictive and non-restrictive) and taking into account the existing practical experience of their implementation. Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activities when considering issues of excise taxation, as well as in determining the priority directions of the tax system development of the Russian Federation.